Tackling the translational challenges of multi-omics research in the realm of European personalised medicine: A workshop report - Oldoni, Emanuela; Saunders, Gary; Bietrix, Florence; Garcia Bermejo, Maria Laura; Niehues, Anna; ’t Hoen, Peter A. C.; Nordlund, Jessica; Hajduch, Marian; Scherer, Andreas; Kivinen, Katja; Pitkänen, Esa; Mäkela, Tomi Pekka; et al. (Frontiers in Molecular Biosciences, 2022)
Personalised medicine (PM) presents a great opportunity to improve the future of individualised healthcare. Recent advances in -omics technologies have led to unprecedented efforts characterising the biology and molecular mechanisms that underlie the development and progression of a wide array of complex human diseases, supporting further development of PM. This article reflects the outcome of the EATRIS-Plus Multi-omics Stakeholder Group workshop organised to 1) outline a global overview of common promises and challenges that key European stakeholders are facing in the field of multi-omics research, 2) assess the potential of new technologies, such as artificial intelligence (AI), and 3) establish an initial dialogue between key initiatives in this space. Our focus is on the alignment of agendas of European initiatives in multi-omics research and the centrality of patients in designing solutions that have the potential to advance PM in long-term healthcare strategies.